0676 Increased Depression Symptoms are Associated with Higher Nightmare Frequency within the Wisconsin Sleep Cohort. (25th May 2022) - Gratton, Matthew; Mazzotti, Diego; Hamilton, Nancy
Abstract: Introduction: Nightmare frequency has been suggested as a strong clinical indicator of psychiatric disorders. Additionally, frequent nightmares are a possible underrepresented outcome of depression. As nightmares may increase the risk of negative health outcomes, such as suicide attempts, understanding possible sources of nightmare frequency is imperative. This study sought to examine the association between depression and anxiety on the incidence of high frequency of nightmares. Methods: Using cross-sectional and longitudinal data from the Wisconsin Sleep Cohort, accessed through the National Sleep Research Resource, we conducted an analysis of demographics, co-occurring sleep disturbances, and mental health measures of participants experiencing ordinal frequencies of nightmares. The study sample included 758 Wisconsin state employees with a baseline and follow-up assessment (mean 4.46 years between visits; standard deviation 1.7). All participants were screened for depression and anxiety symptoms using the Zung Depression Scale (SDS), and the State-Trait Anxiety Inventory. Sleep disturbances, medication use, nightmares and insomnia were based on self-report. Nightmare frequency was categorized as high (≥2 per month) and low (<2 per month). Logistic regression was used to determine the association of baseline anxiety and depression scales (in the same model) with incidence of high nightmare frequency at follow-up, adjusted by age, sex, body mass index, hypertension medications, use of narcotics and caffeine. Results: After adjusting for covariates, SDS scores at baseline were associated with an increased incidence of higher frequency of nightmares at follow-up (OR=1.05; 95%CI=1.01-1.10, p = 0.026), while anxiety at baseline was not (OR=1.03; 95%CI=0.99-1.07; p = 0.165). An increase in one unit of the SDS was associated with a 5% increase in the odds of presenting higher frequency nightmares at follow-up. Conclusion: Participants with higher SDS scores had higher incidence of high frequency of nightmares upon follow up, however, those with anxiety did not. Further research should be targeted at gaining better understanding of the role of psychiatric conditions on the onset of nightmares. Support (If Any): NIH NHLBI (R01HL62252), NIA (R01AG036838, R01AG058680), and National Center for Research Resources (1UL1RR025011). The National Sleep Research Resource was supported by NIH-NHLBI (R24 HL114473, 75N92019R002).